The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1088/1674-4926/35/1/013001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal migration route of Cu in HfO2

Abstract: The movement of Cu in a HfO 2 -based resistive random access memory (RRAM) device is investigated in depth by first-principle calculations. Thermodynamics analysis shows that the dominant motion of Cu tends to be along the [001] orientation with a faster speed. The migration barriers along different routes are compared and reveal that the [001] orientation is the optimal migration route of Cu in HfO 2 , which is more favorable for Cu transportation. Furthermore, the preferable HfO 2 growth orientation along [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These models are classified as Kinetic Monte Carlo, 8,9) Finite Element Method, and atomistic models. [10][11][12][13][14][15][16][17][18][19][20][21][22] The growth time of conductive filaments can be gotten by calculating the drift and diffusion equation of ions in these models. Although these models can describe the growth and dissolution of conductive filaments more accurately, most of them are numerical models.…”
Section: Introductionmentioning
confidence: 99%
“…These models are classified as Kinetic Monte Carlo, 8,9) Finite Element Method, and atomistic models. [10][11][12][13][14][15][16][17][18][19][20][21][22] The growth time of conductive filaments can be gotten by calculating the drift and diffusion equation of ions in these models. Although these models can describe the growth and dissolution of conductive filaments more accurately, most of them are numerical models.…”
Section: Introductionmentioning
confidence: 99%
“…As the mainstream, flash memory has encountered a bottleneck in the 32 nm process, to find a new storage mechanism to replace flash memory technology has become an inevitable trend in the development of memory. And among a variety of new memory technology, the Resistive Random Access Memory (ReRAM) has the advantages of simple structure, fast read and write speed, low manufacturing cost, low power consumption and compatibility with CMOS process [1,2,3,4,5]. So it is considered as an excellent memory for the replacement of flash memory technology [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-electrolyte-based resistive random switching memory (ReRAM) based on transition metal oxides (TMOs), also known as electrochemical metallization (ECM) cells, is a very attractive candidate to replace flash memory due to its simple metal-insulator-metal (MIM) sandwich structure, [1] high density, long retention time, excellent scalability, low power consumption, [2][3][4][5] and compatibility with CMOS technology. Among a wide variety of TMOs [6][7][8][9][10][11][12][13][14][15][16][17][18][19] (HfO 2 , ZrO 2 , SiO 2 , TiO 2 , Ta 2 O 5 , etc.) that have been proposed thus far, HfO 2 is particularly attractive due to its possible role in replacing silicon dioxide as the gate dielectric in a CMOS logic transistor and also due to its good resistive switching (RS) capability.…”
Section: Introductionmentioning
confidence: 99%
“…As described by Tingkun Gu's model, the conductive path in Cu-based Ta 2 O 5 along [001] orientation has been observed by studying the isosurface plot of the partial charge density. [17] Lu et al [18] discussed the optimal migration path of Cu in HfO 2 along the [001] direction, which is helpful for reducing power consumption in HfO 2 based ReRAM. Liu et al [19] have observed a conductive filament in Ag-based SiO 2 within the (111) plane by using transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%